MATARANINE A AND B: A NEW DIASTOMERIC INDOLE ALKALOID FROM Alstonia scholaris R.Br. OF LOMBOK ISLAND - Surya Hadi (Universitas Gadjah Mada, 2009)
Alstonia scholaris R. Br., (Apocynaceae) is widely distributed in Indonesia and in Lombok Island, the plant locally known as